2008
DOI: 10.1128/aac.00189-08
|View full text |Cite
|
Sign up to set email alerts
|

SGI2, a Relative ofSalmonellaGenomic Island SGI1 with an Independent Origin

Abstract: Multiply antibiotic-resistant Salmonella enterica serovar Emek strains isolated in Australia and the United Kingdom had similar features, suggesting that they all belong to a single clone. These strains all contain SGI2 (formerly SGI1-J), an independently formed relative of Salmonella genomic island SGI1. In SGI2, the complex class 1 integron which includes all of the resistance genes is not located between tnpR (S027) and S044 as in SGI1 and SGI1 variants. Instead, tnpR was found to be adjacent to S044, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
62
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 41 publications
3
62
0
Order By: Relevance
“…1A). However, the right boundary PCR product was 2.1 kb larger than the size expected from the SGI1-J (SGI2) sequence with the GenBank accession number AY963803 (11). Sequence analysis revealed that, adjacent to the short segment of 152 bp derived from the IRt outer end of Tn402, the complex integron of serovar Virchow strains harbored the right outer end of the mercury resistance transposon Tn5058 (GenBank accession no.…”
Section: Dfra1-orfcmentioning
confidence: 99%
See 4 more Smart Citations
“…1A). However, the right boundary PCR product was 2.1 kb larger than the size expected from the SGI1-J (SGI2) sequence with the GenBank accession number AY963803 (11). Sequence analysis revealed that, adjacent to the short segment of 152 bp derived from the IRt outer end of Tn402, the complex integron of serovar Virchow strains harbored the right outer end of the mercury resistance transposon Tn5058 (GenBank accession no.…”
Section: Dfra1-orfcmentioning
confidence: 99%
“…Sequence analysis showed the presence of the trimethoprim resistance gene cassette dfrA1 and a gene cassette of unknown function, orfC. These results suggested the occurrence of the SGI1-J complex integron variant recently described in serovar Emek strains (11). Then, PCRs were carried out from the sul1⌬ gene to the tetR gene and the resulting product was sequenced.…”
Section: Dfra1-orfcmentioning
confidence: 99%
See 3 more Smart Citations